Autobiography of Brook Farm - Sams, Henry W. (Englewood Cliffs, New Jersey Prentice-Hall, 1958)
The story of the experimental community that included Nathaniel Hawthorne and Charles Dana is related through this collection of materials pertaining to the rise, development, and fall of Brook Farm.
Includes index.
Keywords: Brook Farm Phalanx (West Roxbury, Boston, Mass.)